2017
DOI: 10.1111/jfpp.13449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mango kernel starch coatings on the shelf life of almond ( Prunus dulcis ) kernels

Abstract: The effect of mango kernel starch (MKS) coatings on shelf life of roasted almonds was determined. The coating formulations were prepared by gelatinizing 4% MKS in distilled water and plasticized with glycerol, sorbitol, and their 1:1 mixture (50% of starch weight; db). Lipid oxidation was evaluated by peroxide value (PV), thiobarbituric acid reactive substances (TBARS), and p‐anisidine (AV) values. Results showed significant differences in coated and uncoated nuts and the rate of oxidation was significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…A similar result was reported by Nawab et al. (2018) for mango starch coatings on almond ( Prunus dulcis ) kernels (Nawab et al., 2018).…”
Section: Resultssupporting
confidence: 89%
“…A similar result was reported by Nawab et al. (2018) for mango starch coatings on almond ( Prunus dulcis ) kernels (Nawab et al., 2018).…”
Section: Resultssupporting
confidence: 89%
“…Fiber rich composition of MSK furnishes low caloric and bulking properties to composite flour and baked goods. MSK has been reported to enhance water and oil retention, emulsion stability, oxidative reactions inhibition, and plasticizing properties (Abdalla, Darwish, Ayad, ; Abdel‐Razik et al, ; Ashoush & Gadallah, ; Legesse & Emire, ; Nawab, Alam, Haq, Lutfi, & Hasnain, in press; Pereira et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…53 Indeed, darkening of edible kernels has been followed by decreased color acceptance. 41,54 However, in a recent study, 52 walnuts coated with walnut protein, although darker than an uncoated control, were not less acceptable than the control, whereas walnuts coated with methylcellulose (MC), perceived as lighter in color, had their acceptance impaired. Grosso et al 11 observed that walnuts with coatings based on cellulose derivatives (MC and CMC) were less acceptable than the uncoated ones, whereas a whey protein coating did not affect the product acceptance.…”
Section: Sensory Outcomes Of Edible Coatings On Kernelsmentioning
confidence: 97%
“…Dark colors may be associated with deterioration, since kernels usually become darker with storage, which is ascribed to enzymatic oxidation of phenolic compounds . Indeed, darkening of edible kernels has been followed by decreased color acceptance . However, in a recent study, walnuts coated with walnut protein, although darker than an uncoated control, were not less acceptable than the control, whereas walnuts coated with methylcellulose (MC), perceived as lighter in color, had their acceptance impaired.…”
Section: Sensory Outcomes Of Edible Coatings On Kernelsmentioning
confidence: 99%